Assessment index tool for green highway in Malaysia - Balubaid, Saeed; Bujang, Mastura; Wan Azahar, Wan Nur Aifa; Foo, Kian Seng; Raja Muhammad Rooshdi, Raja Rafidah; Hamzah, Norhaliza; Mohd Yazid, Yazlin Salfiza; Abd. Majid, Muhd Zaimi; Mohamad Zin, Rosli; Zakaria, Rozana; Hainin, Mohd Rosli; Yaacob, Haryati; et al. (UTM Press, 2015)
Green highway is a highway project that has been designed and constructed with the sustainability requirements and global standard. Basically, green highway is one of the major parts for sustainable concept where three major aspects are addressed which are economic, social and environment. The main focus for economic aspect is to increase profitability by making more efficient use of resources especially material, improve the quality of life by fulfilling the nation’s need for social aspect while protecting the environment from the impact of CO2 emission and using of natural resources efficiently for the purpose of environment aspect. Therefore, it is important for highway stakeholders to incorporate sustainable criteria in their projects. The implementation of sustainable concept in highway needs to be evaluated by green highway rating tool assessment. Thus, the purpose of this study is to establish a tool to assess and certify a green highway in Malaysia. The data for this study was obtained through group discussion with highway experts and questionnaires that were distributed to identify the sustainability factors. Then the data were analyzed using factor analysis method. The findings of this study indicated that, there are five major sustainable factor which are Sustainable Design and Construction Activities, Social and Safety, Energy Efficiency, Environmental and Water Management and Material and Technology that are included in the development of green highway rating system.